Post myocardial infarction ionic remodelling promotes repolarisation dispersion and electrocardiogram abnormalities in acute and chronic stages. (24th May 2021) - Wang, ZJ; Zhou, X; Tomek, J; Wang, L; Rodriguez, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Wellcome Trust Background: Sudden cardiac death (SCD) occurs in both acute and chronic stages post myocardial infarction (MI), and the left ventricular ejection fraction (LVEF) and electrocardiogram (ECG) characteristics are important biomarkers for clinical decision making. While various ionic remodelling has been reported in literature at various stages post-MI, the effect of them on clinical biomarkers have not been fully explored. Purpose: Evaluate the effects of cellular ionic remodelling in acute and chronic post myocardial infarction on ECG and LVEF biomarkers through computational modelling and simulations of human biventricular electromechanics. Methods: An electromechanical coupled biventricular model with ToR-ORd (Tomek 2019) human electrophysiology coupled with human excitation-contraction machinery (Land 2017) and orthotropic passive mechanics (Holzapfel 2009) was used as baseline model. The 12-lead ECG were simulated at standard body-surface electrode locations, and the biventricular pressure volume loop was simulated to quantify the simulated LVEF. A cardiac magnetic resonance (CMR) derived human biventricular geometry (Strocchi 2020) was used in combination with rigidly aligned torso geometry (Minchole 2019). An anterior sub-endocardial infarction was delineated with infarct, border zone (BZ) and remote zone (RZ) regions. For acute infarction, three types of BZ ionic remodelling from literature, and their effects on simulated LVEF and ECG characteristics were quantified. For chronic infarction, a single chronic BZ ionic remodelling was combine with two different models of RZ ionic remodelling from literature, and the effects of these remodelling on the simulated LVEF and ECG were quantified. The electromechanical properties of the sub-endocardial infarct region did not significantly affect simulated ECG or LVEF biomarkers. Results: For the acute phase, simulations showed pre-cordial ECG abnormalities for all three BZ models, with T-wave inversion and QT prolongation (80 ms) in BZ1, ST-segment elevation with T-wave inversion in BZ2, and decreased T-wave amplitude in BZ3. Activation maps showed conduction block in BZ2 simulations, leading to ST-segment elevation. Repolarisation maps showed high dispersion in BZ1 simulations, leading to T-wave inversion. LVEF for BZ2 decreased by 4% (from 57% in control) due to conduction block in BZ and lack of contraction in that region, LVEF remained constant for BZ1 and BZ3 simulations. For the chronic phase, there was QT prolongation in both RZ1 (80 ms) and RZ2 (170 ms) as well as decreased T-wave amplitude, reflected by elevated repolarisation dispersion. LVEF was not significantly altered for either simulations. Conclusions: Post-MI ionic remodelling at the acute and chronic stages cause varying degrees of dispersion of repolarisation and T-wave and ST-segment abnormalities, with minimal effect on mechanical function, except in the case of severe conduction abnormality.